MENENTUKAN OPSI BELI BARRIER DOWN AND OUT TIPE EROPA DENGAN VOLATILITAS MODEL GARCH (Studi Kasus Saham Melco Crown Entertainment Limited) - , LARAS NUR NOVIANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A derivative product is a financial contract which derives its value from the performance of another entity such as an asset, bond, or interest rate. One of the most popular derivative is European down and out barrier call option. It is an option with barrier level at under price of asset and option is extinguished on the price of the underlying asset breaching a barrier. This option is used to take advantage of underlying asset that always on the top. Pricing down and out barrier option can be determined with Black-Scholes formula. All parameters in the Black-Scholes formula, exercise price (K), time to maturity (T), price of asset at t=0 (ð0) , barrier value (B), risk free interest rate (r) can be known, except a volatility (Ï). This research is tell about how to estimate volatility with GARCH model to pricing European down and out barrier call option. Where GARCH model is a simple model and its not only dependent to before residual data, but also dependent to before volatility. Beside that GARCH model can be overcome volatility clustering in return data